PENGARUH SENAM LANSIA TERHADAP KESEIMBANGAN TUBUH PADA LANSIA DI LINGKUNGAN DAJAN BINGIN SADING - Meril Valentine Manangkot; Wayan Sukawana; Made Surata Witarsa (Coping: Community of Publishing in Nursing, 2016)
Aging process results in decreasing the ability of the body's tissue. One of it is muscle tissue that cause body balance disorder on elderly. One way that can be done to overcome the body balance disorder is by doing elderly exercise regularly. This research aimed to identify the effect of elderly exercise to body balance on elderly in Dajan Bingin Sading. The method used in this study was pre-experimental with one group pretest-posttest design. The sample amounted to 27 people were gotten through purposive sampling technique. The data was collected through observation with the Berg Balance Scale check list. The pre-exercise measurement showed that majority of respondents had mild balance disorders (63%), whereas post-exercise result revealed that majority of respondents had good body balance (51,9%). The result of data analysis showed that there is effect of elderly exercise to body balance on elderly in Dajan Bingin Sading with p value=0,001 (p?0,05). Based on this result, it is suggested to the elderly to do elderly exercise regularly to overcome the body balance disorder along their aging processes.